How media constructs political corruption: case of media reaction to the political corruption scandal during political election campaign - Matkevičienė, Renata (Political Preferences, 2017)
Corruption is not just a problem ofdeveloping countries, corruption scandals arise and developin Western democracies, and only the perception and assessment of corruption differ. As scientists state corruptionis a phenomenon that is determined by the country's democratic (state) traditions, and culture, dominant values and behaviour standards, etc. Most of the time corruption is analysed in the context of political, business, health care, media systems, that are interrelated. By far talking about the understanding and reaction to corruption in politics, are based on public perception of corruption. Corruption in political arena is related not only with actions of politicians, or public officers, but depends on the understanding and tolerating it in society. The cases of political corruption are rare, but still happening in various countries, in no relation are those developing countries, the newly established democracy, or so called western democracies. The phenomenon of political corruption is based on political culture, or even more broadly on national culture, traditions. And because of that cases of political corruption and their evaluation and reaction by the participants of political system (political actors, media and citizens) in general demonstrates the level of tolerance of such actions. As the mirror of perception of political corruption in political system the result of political election campaigncould be taken to account, because it demonstrates the activities of all participants of political system and their their attitude toward the case. This article aims to analyze conception of political corruption in order to identify main determinants of it and to investigate potential influence ofthe case of corruption of political actortothe outcome of the political elections. In this paper the quantitative media content analysis is presented to show the coverage of the political party in relation to political election campaign during the political election period and political corruption event in search for the factors to determine the presentation and possible impact of political corruption event to the results of political elections. In the research the media content of the political actor, that was accused for corruptive activities (for bribe) was analysed. Also article discusses whether the political corruption of political party leaderand its presentation in media may affect the political election results. Key words: corruption, political corruption, bribery, corruption scandal, media, elections